Promoting Religious Moderation Among Bandung's Youth: Insights from SALIM Community - Pratama, Predi M.; Turmudi, Hamzah (Jurnal Iman dan Spiritualitas, 2024)
This research is aimed at finding out how Sahabat Lintas Iman (SALIM) organizes activities containing the value of religious moderation, analyzed using Anthony Giddens' theory regarding social movements. By using this sociological approach, the author tries to reveal the facts in the field regarding the socialization of religious moderation to the young generation of Bandung. The method used is descriptive by presenting the social phenomena obtained in narrative form. The type of data in this research is qualitative, equipped with data collection techniques through observation and interviews. In the research, data was found regarding the socialization of religious moderation carried out by the SALIM community to the young generation of Bandung. Researchers found three activities that have religious moderation values, namely: First, religious cafes are a place that combines enthusiastic young people with the experience of wise parents. Not just a meeting, but also an encounter that builds mutual understanding that inspires new perspectives. Second, the tour of places of worship is one of SALIM Bandung's programs in socializing religious moderation to the young generation of Bandung. The activities take place when one religion is celebrating its religious holiday. Third, the Interfaith Friends Meeting (PASINI) is a meeting between religious followers, without feeling low or high and without any secret agenda or goals.